Theatres of blood: Performative violence in Iraq. Issue 2 (1st June 2018) - Tripp, Charles
This article examines much of the violence of the past two decades in Iraq through the prism of performative politics. This draws attention to its spectacular nature, its repertoires and aesthetics, where blood becomes the common referent in a theatre of state power and resistance. Beyond the spectacle, however, violence is performative in that it possesses causal power. Violence has shaped the ways in which conflicts have been understood and organized, reproducing and reinforcing particular identities, institutions and attitudes in Iraq. Performative violence became a spectacle of horror and, through that horror a technology for the demarcation of whole categories of Iraqi citizen whose blood Islamic State and others licensed themselves to shed. Both nascent state forces and those resisting them, as well the foreign powers active in the Iraqi theatre, had every interest in making manifest their competence and their potential in the use of violence. Regardless of the identity of the parties involved, or the ends they were pursuing, violence has thus become a key technology of power. To perform it has been to assert the right to power in the political landscape of Iraq.